Graphene-based frustrated Lewis pairs as bifunctional catalysts for CO2 reduction via the dissociative chemisorption of molecular H-2: a periodic density functional perspective - Senthamaraikannan, Thillai Govindaraja; Krishnamurty, Sailaja; Kaliaperumal, Selvaraj (New Journal of Chemistry, 2021)
Nanocarbon-based frustrated Lewis pair (FLP) bifunctional catalysts, on account of their unquenched electron transfer property, are becoming increasingly attractive as catalysts for the CO2 reduction reaction via the dissociative chemisorption of H-2. In the present study, we propose a nanocarbon-based FLP catalyst. The pair comprises nitrogen doped/phosphorus doped graphene as Lewis bases and M(C6F5)(3) (M = B, Al, Ga, and In) as Lewis acids. The computational investigation reveals that the carbon atoms adjacent to the doped N and P atoms are the active sites towards the dissociative chemisorption of hydrogen molecule. The analyses of the Bader charges and difference charge densities validate the dissociative chemisorption of H-2 molecule and the fact that a significant electron redistribution promotes the polarization of the hydrogen molecule. Density of states confirms the hybridization between the p-states of the nitrogen/phosphorus atom and the s-state of hydrogen atom in all FLPs. The dissociative chemisorption of hydrogen is noted in all FLP complexes, thereby facilitating a low barrier reaction path for CO2 reduction. Between P-doped and N-doped FLPs, N-doped FLP catalysts prove to be a more promising counterpart with considerably low activation barriers, ranging between 0.01 and 0.11 eV, towards CO2 reduction. Thus, the present study demonstrates the great potential of doped carbon-based FLPs as novel nanostructure catalysts for CO2 reduction via the direct utilization of molecular hydrogen.

Role of chemical structure of support in enhancing the catalytic activity of a single atom catalyst toward NRR: a computational study - Senthamaraikannan, Thillai Govindaraja; Kaliaperumal, Selvaraj; Krishnamurty, Sailaja (Frontiers in Chemistry, 2021)
Using the periodic density functional theory–based methodology, we propose a potential catalytic system for dinitrogen activation, viz., single metal atoms (Mo, Fe, and V) supported on graphene-based sheets. Graphene-based sheets show an excellent potential toward the anchoring of single atoms on them (Mo, Fe, and V) with adsorption energies ranging between 1.048 and 10.893 eV. Factors such as defects and BN doping are noted to enhance the adsorption energies of single metal atoms on the support. The adsorption of a dinitrogen molecule on metal atom–anchored graphene-based supports is seen to be highly favorable, ranging between 0.620 and 2.278 eV. The adsorption is driven through a direct hybridization between the d orbitals of the metal atom (Mo, Fe, and V) on the support and the p orbital of the molecular nitrogen. Noticeably, BN-doped graphene supporting a single metal atom (Mo, Fe, and V) activates the N2 molecule with a red shift in the N–N stretching frequency (1,597 cm−1 as compared to 2,330 cm−1 in the free N2 molecule). This red shift is corroborated by an increase in the N–N bond length (1.23 Å from 1.09 Å) and charge transfer to an N2 molecule from the catalyst.